Sociodemographic and Health Insurance Ownership Related to Tuberculosis in Elderly: An Analysis of Indonesia Health Survey - Lili Amaliah; Oktia Woro Kasmini Handayani; Intan Zainafree (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Tuberculosis (TB) continues to be a significant public health issue globally, with Indonesia being one of the nation’s experiencing the highest TB burden in the world. The purpose of this study is to analyze the sociodemographic factors and health insurance ownership associated with the incidence of tuberculosis (TB) among the elderly in Indonesia. Methods: This study used secondary data from the 2023 Indonesia Health Survey (SKI), focusing on elderly individuals (?60 years). A total of 97,339 participants were included after applying inclusion criteria. The dependent variable was the self-reported diagnosis of tuberculosis (TB), and independent variables included age, sex, marital status, education, occupation, health insurance, place of residence, and family status. Data were analyzed with univariate, bivariate (Chi-square), and multivariate (binary logistic regression) analyses. Results: The study found that 0.57% of older adults self-reported the tuberculosis diagnosis. The significant associations between tuberculosis diagnosis and variables such as sex, marital status, education, occupation, health insurance, place of residence, and family status, with women, higher education levels, certain occupations, health insurance coverage, urban living, and being head of the household being less likely to report TB, while age showed no significant association. The binary logistic regression revealed that factors such as sex, education, occupation, health insurance, and family status significantly influence the likelihood of TB diagnosis, with females, higher education levels, certain occupations, no health insurance, and being a spouse showing reduced odds of being diagnosed with TB. Conclusion: This study found that tuberculosis (TB) among older persons was significantly associated with several sociodemographic factors, including sex, education level, occupation, health insurance ownership, and family status. Female older adults and those with higher education levels were less likely to be diagnosed with TB. Similarly, those who were employed, especially as private employees, entrepreneurs, or farmers, and those without health insurance had lower odds of TB. It is suggested to improve TB prevention and treatment strategies for older adults, with a particular emphasis on gender, education, employment, and health insurance access.